Clinical analysis and predictive value of early serum lipid levels in very premature and extremely preterm infants with bronchopulmonary dysplasia: a 4 years retrospective study - Zhenyu Xiong; Lei Hang; Qingxiong Zhu (BMC Pediatrics)
Abstract Background Lipid metabolism plays an important role in fetal growth and development, but its role in lung maturation is currently unknown. We investigated the relationship between early serum lipid levels and clinical characteristics of bronchopulmonary dysplasia (BPD) in very preterm and extremely preterm infants. Methods This study analyzed the clinical data of preterm infants with gestational age ≤ 32 weeks between January 2020 and February 2024, while clinical risk factors, maternal comorbidities, treatment methods and prognosis were retrospectively reviewed for subjects (n = 341) recruited from neonatal intensive care unit (NICU). Results Of 228 BPD and 113 non-BPD extremely preterm infants, univariate analysis found that triglyceride (TG, P < 0.01) and high-density lipoprotein (HDL, P = 0.04) levels on the first day of admission were significantly lower in BPD infants, however, apolipoprotein A1 levels were higher than those in the non-BPD group (P < 0.01). Multivariable model further revealed that apolipoprotein A1 (Apo-A1) was a dominant determinant (OR 6.55, 95% CI 2.61,6.12). Regarding perinatal risk factors, maternal gestational hypertension was a risk factor for the morbidity of BPD (P = 0.04), while prenatal hormone exposure displayed a positive performance (P = 0.01). Kaplan-Meier curve showed no statistical difference in survival between low and normal serum lipid level groups (P > 0.05). Conclusions TG, HDL, Apo-A1 levels provide an insight risk and prognostication stratification in very preterm BPD infants, thus, neonatologists should emphasize high-risk features and optimize preventive therapy.